Measuring the Impact of Real Estate Credit Expansion on the Chinese Economy (2008 - 2018) - Jiahao, Pan; Burlakov, Georgi; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
The main research objective of this thesis was to empirically explore the degree of debt default risk faced by Chinese real estate enterprises in the context of the bankruptcy of Evergrande Group and the subsequent measures taken by the Chinese government to protect the domestic market. The theoretical part of this paper aims to clarify the process of capital structure adjustment. The optimal capital structure theory is obtained by describing and comparing different capital theories. The purpose has been to summarize the existing views in the economic literature what is the impact of debt growth on the enterprise performance and summarize the arguments why it could not be optimal for the company to increase its debt continuously. The ultimate generalization of all the theories described could be that the change of company value with debt can be roughly divided into two stages. In the first stage, the bankruptcy cost is small when the company's debt level is low. In this stage, the company value rises rapidly with the increase in debt. In the second stage, when the debt level rises to a certain level, the company's value is maximized. According to the marginal effect analysis, the marginal tax avoidance income and marginal bankruptcy cost of the debt are equal. In the second stage, after critical level of debt is accumulated, the value of the company will gradually decrease with the further increase of the debt level. Next as a motivation for the research on the realization of the theoretic concepts in the Chinese real-estate market, an overview of the historical development of the latter is made. It provide historical background what caused the current high debt of China's real estate enterprises, and comments on the role of the Chinese government issued the "three red lines" policy the expansion of the debt default risk of Evergrande Group in year 2021.
The case of the Evergrande Group is given as an example that raises concerns about having other domestically listed real estate enterprises being threatened to experience the same difficulties covering their debt duties soon. This was adopted as a hypothesis to be empirically verified. Therefore, in the empirical part, data was extracted for 272 companies operating in China's real estate market from 2008 to 2021. For the purpose, companies have been divided into two samples. Respectively, if the enterprises that were active through the whole period explored from 2008 to 2021, they were implied to be well-established and therefore assigned to the first sample titled “core stocks”. In the second sample, titled “other stocks” all the rest were included. The two samples have been analyzed separately to determine the possible differences in default risk. Comparing the debt capital ratio distribution of core companies and other companies, suggests that the stocks of the top 10% of companies in debt ranking have increased. The core stocks are almost twice as many as other stocks. The distribution comparison of distance-based S&P ratings shows that the stocks of core stocks and other AAA (highest and lowest risk rating categories) have rapidly declined. In contrast, the share of stocks corresponding to the level of risk of intermediate rating categories BB and BBB expanded. No core company was identified to enter the high-risk bottom rating category CCC so that no evidence could be provided for any of the enterprises in this sample to be threatened by bankruptcy in the short run. The results for the sample of “other” stocks were just marginally more volatile but still concentrated within the middle rather than hi-risk segment of the S&P rating scale In summary, the main conclusion made in the thesis is that even though the calculated debt capital ratio, default distance, and default probability indicate that for the stocks analyzed, the debt, median default p
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses